1992
DOI: 10.1016/0376-7388(92)80134-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures in phase-inversion membranes. Part 1. Formation of macrovoids

Abstract: A new mechanism for the formation of macrovolds m phase-mverslon membranes IS proposed It 1s based on the observed difference m type of demlxmg of a thm film of a polymer solution when immersed m a nonsolvent bath delayed or instantaneous demlxmg The explanation for macrovold formation assumes local condltlons of delayed demlxmg m front of a certain layer of nuclei already formed, due to a change m mterfaclal composltlons at the advancing coagulation front, as compared to the ongnal composltlon at the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
461
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 826 publications
(497 citation statements)
references
References 16 publications
31
461
0
5
Order By: Relevance
“…That is due to that the dope solution and bore fluid (water) are co-extruded through the spinneret, and the diffusion exchange between the solvent and non-solvent is instantaneous that results in a highly unstable dope solution so that a rapid demixing process occurs. Such condition favors the formation of cellular-like macrovoid structures [40]. In the transition layer, located in the middle of the membrane, spongy-like structure is formed due to the delayed phase transition process.…”
Section: Resultsmentioning
confidence: 99%
“…That is due to that the dope solution and bore fluid (water) are co-extruded through the spinneret, and the diffusion exchange between the solvent and non-solvent is instantaneous that results in a highly unstable dope solution so that a rapid demixing process occurs. Such condition favors the formation of cellular-like macrovoid structures [40]. In the transition layer, located in the middle of the membrane, spongy-like structure is formed due to the delayed phase transition process.…”
Section: Resultsmentioning
confidence: 99%
“…La formation de ces différentes structures morphologiques a été attribuée par de nombreux auteurs à la séparation de phase lors de la coagulation (Reuvers et al, 1987 ;Smolders et al, 1992 Par ailleurs, l'aptitude de ces membranes à retenir des cations laisse à supposer qu'au cours de la coagulation, les molécules d'eau qui pénètrent dans la matrice de la membrane attirent les groupes carboxyliques, provoquant ainsi une orientation préférentielle de ces groupes vers le centre des structures poreuses. Par conséquent, les groupes carboxyliques sont préférentiellement distribués à l'interface des pores et sur les surfaces membranaires.…”
Section: Détermination De La Concentration Des Ions Métalliques Et Deunclassified
“…It was found that with asymmetric membranes, the porosity increases with the increase of the immersion bath temperature [47]. Raising the temperature increases mutual diffusivities between the nonsolvent (as water) and the solvent (as DMF) in the casting solution during demixing process.…”
Section: Effect Of Immersion Bath Temperature (Ibt)mentioning
confidence: 99%